Case report: Cerebrospinal fluid neutrophilic pleocytosis upon intrathecal triamcinolone injection - Tsaktanis, Thanos; Stritzelberger, Jenny; To, Vi Tuong Daniel; Uhl, Martin; Schwab, Stefan; Heuss, Dieter; Rothhammer, Veit (Frontiers in Neurology, 2024)
Intrathecal corticosteroids, initially employed in the 1950s, faced declining use due to complications like arachnoiditis and aseptic meningitis. Triamcinolone, which is nowadays used as intrathecally applied glucocorticoid formulation, has been shown to beneficially influence spasticity without demonstrable influence on disease activity or progression. We here present the case of a patient with recurrent episodes of aseptic cerebrospinal fluid (CSF) neutrophilic pleocytosis over a year following intrathecal triamcinolone treatment. CSF analyses revealed a post-injection CSF cytokine profile resembling cytokine release reaction rather than drug hypersensitivity. This case thus highlights a potential side effect of intrathecal triamcinolone injection with yet unclear clinical relevance, underscores the need for further assessment of clinical benefits of intrathecal triamcinolone, and emphasizes potential short and long-term side effects associated with extended intrathecal triamcinolone use.